Analisis Kemampuan Membaca Al-Qur’an Mahasiswa Fakultas Hukum Universitas Lampung - Friyansyah; Eka Suci Indria Sari; Rohani; Ujang Efendi (Institut Agama Islam Darul Fattah Lampung, 2024)
The pandemic several months ago had an impact on PAI's lecture patterns, especially on increasing Al-Qur'an learning in public universities. Online lectures require lecturers and students to teach and learn from their respective homes. The aim of PAI learning in public universities is the development of students' Islamic personality, the development of Muslim personality traits that adhere to the teachings of their religion. The skill of reading the Al-Qur'an is the key to achieving PAI lectures, as an achievement that cannot be separated from achieving understanding in other material. However, there are factors inhibiting learning the Koran, including low motivation from students, lack of discipline, changing learning patterns from high school to college, online learning. The research objective to be achieved is as follows: